Thermal Environment and Energy Performance of a Typical Classroom Building in a Hot-Humid Region: A Case Study in Guangzhou, China - Liang Yi; Yuan Xie; Chang Lin (Geofluids)
Buildings and the construction sector account substantially for global energy consumption. In hot-humid areas of China, suboptimal thermal comfort in classrooms has heightened their cooling load and energy consumption. It is necessary to renovate the buildings of outdated code according to the current weather conditions to save energy. This study thus aimed to examine the thermal effects of such designs on the cooling load, based on an actual classroom building during summers in hot-humid southern China. Using air temperature and PMV values to evaluate thermal comfort, this study conducted simulation through EnergyPlus and DesignBuilder. The resultant updated typical meteorological year (TMY) and the monthly and hourly analyses of indoor thermal comfort revealed persistent classroom overheating. To mitigate the cooling load, numerous design variables were investigated: space form, roofing, external walls, windows, and shading devices. Evaluative comparisons found that appropriate choice of external windows and shading devices represented the two most effective strategies in mitigating the cooling load. Furthermore, jointly applying effective retrofit strategies to the building yielded a favorable reduction in the annual cooling energy consumption by 16.6%. The findings herein are envisioned to provide evidence-based referential guidance for building designs for classrooms in a hot-humid climate.